2000
DOI: 10.1603/0046-225x-29.5.1060
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior of Two Acridid Species: Effects of Habitat and Season on Body Temperature and the Potential Impact on Biocontrol with Pathogens

Abstract: Thermoregulatory behavior was studied in two key acridid pest species from west and south Africa. Locustana pardalina Walker (Orthoptera: Acrididae) from the arid Karoo region of South Africa was an active behavioral thermoregulator using postural adjustments and microhabitat selection to elevate and then maintain body temperatures at a preferred level between 38 and 41ЊC for much of the day. Both cool weather and time of season signiÞcantly affected the ability of these locusts to reach and maintain these pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 33 publications
(43 reference statements)
1
33
0
1
Order By: Relevance
“…Hinks and Erlandson (1994) opined that temperature is a very important and determining factor for grasshopper rearing. Moreover, it has been reported that reproductive potential in grasshopper is highly temperature dependant (Whitman 1998;Blanford and Thomas 2000). Das et al (2012) insects produce a biomass of 18.48 ± 1.67 g wet weight in one generation.…”
Section: Discussionmentioning
confidence: 99%
“…Hinks and Erlandson (1994) opined that temperature is a very important and determining factor for grasshopper rearing. Moreover, it has been reported that reproductive potential in grasshopper is highly temperature dependant (Whitman 1998;Blanford and Thomas 2000). Das et al (2012) insects produce a biomass of 18.48 ± 1.67 g wet weight in one generation.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance of locusts and grasshoppers to disease is strongly affected by temperature and the thermoregulatory behavior of the infected host (27)(28)(29)(30). Studies have shown that gregaria desert locusts enhance their resistance to M. anisopliae var.…”
Section: Methodsmentioning
confidence: 99%
“…Many acridids, particularly those that live in seasonally constrained environments (Whitman, 1988), or environments that have large diurnal fluctuations in temperature (Blanford and Thomas, 2000), use basking and/or selection of thermal microenvironment, to gain a measure of control over body temperature. It is thought that these behaviorally thermoregulating acridids have a preferred, Archives of Insect Biochemistry and Physiology or "set point," body temperature that they aim to maintain for as long as possible given suitable environmental conditions.…”
Section: Introductionmentioning
confidence: 99%